Phase evolution in mixture of cobalt and fullerene deposited from vapor. (July 2016) - Lavrentiev, V.; Stupakov, A.; Barchuk, M.; Lavrentieva, I.; Pokorný, J.; Vacik, J.; Čapková, P.; Dejneka, A.
Abstract: Recently we reported the evidence of solubility of Co in solid C60 found from magnetization of the Cox C60 mixture films (Phys. D: Appl. Phys. 48, 2015, 335002). In the present study we identified the Co solubility limit ( x c = 2) and specified phase evolution in the Cox C60 mixtures in a wide interval of the Co concentrations (0 < x < 50) that was carried out through systematic characterization of the film surface morphology, chemical and phase composition. The effect of air exposure allowed us to recognize three intervals of x where phase evolution is controlled by rather different mechanisms. In the first interval (0 < x < 2, dilute mixtures) the phase evolution yields two separated phases, namely fcc-C60 and Co2 C60 . The dilute films do not include Co clusters and almost insensitive to the air exposure. Within the second and third intervals (supersaturated mixtures) designated as x c < x < x m and x m < x, respectively ( x m = 10÷15), the formation of the Co clusters dominates in the phase evolution, which are found to be sensitive to the air exposure. The Co clustering in the mixtures from the second interval is completed by formation of critical nuclei. Within the third interval of x the phase evolution is controlled by growth of the Co clusters due to coalescence process.